2007
DOI: 10.1007/s00277-007-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 and codon 72 P53 polymorphism in multiple myeloma

Abstract: The GSTM1 and GSTT1 genes reduce the effects of exposure to cytotoxic agents. Both genes have a null variant allele in which the entire gene is absent. On the other hand, a common polymorphism of the tumour suppressor P53 gene results in either arginine (A) or proline (P) at amino-acid position 72. The A and P alleles code proteins with distinct functions in apoptosis and DNA repair and have been associated with variable risks for several cancers. However, their roles in multiple myeloma (MM) are still unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
2
18
1
3
Order By: Relevance
“…We also included eligible study with hand searching [31]. By searching “p53”, “polymorphism” and “lymphoma” or “myeloma”, and a hand search from references of original studies or review articles, we included another seven articles [16], [17], [32], [33], [34], [35], [36]. The genotype distributions among the controls of all studies were in agreement with Hardy-Weinberg equilibrium except for three studies [16], [33], [36](Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also included eligible study with hand searching [31]. By searching “p53”, “polymorphism” and “lymphoma” or “myeloma”, and a hand search from references of original studies or review articles, we included another seven articles [16], [17], [32], [33], [34], [35], [36]. The genotype distributions among the controls of all studies were in agreement with Hardy-Weinberg equilibrium except for three studies [16], [33], [36](Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The genotype distributions among the controls of all studies were in agreement with Hardy-Weinberg equilibrium except for three studies [16], [33], [36](Figure 1). As a result, a total of thirteen studies met the inclusion criteria and were identified as eligible articles with 2,711 cases and 7,356 controls, including nine studies of leukemia [15], [31], [37], [38], [39], [40], [41], [42], [43], three studies of lymphoma [17], [32], [34] and one study of myeloma [35]. The selected study characteristics were listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione-S-transferases (GSTs) conjugate phase I activated metabolites to favour their excretion from the organism. Polymorphisms in the GSTM1, GSTT1 and GSTP1 loci have been investigated in several case-control studies with weak evidence of association (102)(103)(104)(105). Although not confirmed in other studies, Lincz et al showed an association between the GSTT1 null genotype and an increased MM risk.…”
Section: Genetic Risk Factors In Multiple Myelomamentioning
confidence: 99%
“…A survey in Campinas (Ortega et al, 2007) analyzed the genes p53 and GSTs in 106 patients with myeloma and 230 controls. The results suggest no positive correlation, but the authors realized that the polymorphism of p53 at the codon 72 combined with null-GSTM1 polymorphism increases the disease progression.…”
mentioning
confidence: 99%